Correction: Behavior-change interventions to improve antimicrobial stewardship in human health, animal health, and livestock agriculture: A systematic review. - Jessica Craig; Aditi Sriram; Rachel Sadoff; Sarah Bennett; Felix Bahati; Wendy Beauvais (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0001526.].